Current Role of Urethrolysis and Partial Excision in Patients Seeking Revision of Anti-Incontinence Sling. Issue 6 (November 2019) - Drain, Alice; Enemchukwu, Ekene; Shah, Nihar; Syan, Raveen; Rosenblum, Nirit; Nitti, Victor W.; Brucker, Benjamin M.
Abstract : Objectives: Stress urinary incontinence is highly prevalent and sling surgery has increased since 2000. Urethrolysis traditionally had been standard management of complications after anti-incontinence surgery; however, partial excision is a less aggressive option. This study describes the different populations in a contemporary cohort that undergo sling excision and urethrolysis and their surgical outcomes. Methods: Chart analysis was performed on patients assigned Current Procedural Terminology codes for removal or revision of sling for stress incontinence, urethrolysis, or revision of graft at our institution from 2010 to 2015. Demographics, indications, outcomes, and subsequent treatment were evaluated. Results: A total of 110 patients underwent surgery and were included. Partial excision was performed on 82 patients and urethrolysis on 28 patients. About 32.7% had prior revision, and median length to revision was 3.1 years. Overall success was 75.0% for urethrolysis and 86.6% for partial excision. Without concomitant sling placement, stress incontinence developed in 25.0% of urethrolysis and 21.6% of partial excision patients. New onset overactive bladder symptoms developed in 21.4% of urethrolysis patients and 7.3% of partial excision, which was significantly different ( P = 0.039). Conclusions: Both approaches had good success, 75.0% for formal urethrolysis and 86.6% for partial excision. New onset urgency was lower for partial excision, but rates of all other complications were similar. These procedures are often used for different patient populations, and thus, outcomes are not meant to be directly compared. Future work on sling revision should report these procedures separately. Abstract : The study describes a contemporary population of patients undergoing sling excision and urethrolysis and explores the outcomes of these distinct procedures.